Perancangan Sistem E-Ticket Berbasis Web di Museum Prabu Geusan Ulun Kabupaten Sumedang Menggunakan Metode Design Thinking - Anggi Siti Padila; Dally Nur Arif; Enjang Yusuf Ali (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The design of the e-ticket system on the Museum Prabu Geusan Ulun website aims to provide users with ease in making digital ticket reservations, with payments made through e-wallets and mobile banking. This system is designed as an innovative feature for reservations to enhance user convenience and comfort. The UI/UX design of the e-ticket system on the Museum Prabu Geusan Ulun website utilizes the design thinking method to create more efficient reservation features using digital payment options. Design Thinking is a method for understanding the needs and challenges faced by users. The objective of this study is to design the UI/UX of the e-ticket system on the Museum Prabu Geusan Ulun website using the Design Thinking method and to conduct usability testing with the Single Ease Question (SEQ) and System Usability Scale (SUS). This research employs a mixed-methods design, combining user interviews for qualitative insights and usability testing as a quantitative approach. The results of the Usability Testing in this study show that the prototype designed is fit for use, with a score of 85.5, which falls into category B or Excellent. This research can serve as a reference for further development and can provide more efficient solutions for users.